1997
DOI: 10.1074/jbc.272.21.13608
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Ligand Binding to the Second Cluster of Complement-type Repeats of the Low Density Lipoprotein Receptor-related Protein

Abstract: The low density lipoprotein receptor-related protein (LRP), a member of the low density lipoprotein receptor gene family, mediates the cellular uptake of a diversity of ligands. A folding chaperone, the 39-kDa receptorassociated protein (RAP) that resides in the early compartments of the secretory pathway inhibits the binding of all ligands to the receptor and may serve to prevent premature binding of ligands to the receptor during the trafficking to the cell surface. To elucidate the molecular interactions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
65
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 36 publications
(42 reference statements)
9
65
0
Order By: Relevance
“…It is as yet unclear how RAP is capable of antagonizing all ligand binding to LRP. In a previous study we have shown that, even though the affinity of RAP for cluster II and LRP is similar, RAP is a poor inhibitor of ligand binding to the isolated cluster II compared with its inhibition of ligand binding to the intact LRP (9). This suggests that RAP does not inhibit ligand binding solely in a competitive or sterical manner.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…It is as yet unclear how RAP is capable of antagonizing all ligand binding to LRP. In a previous study we have shown that, even though the affinity of RAP for cluster II and LRP is similar, RAP is a poor inhibitor of ligand binding to the isolated cluster II compared with its inhibition of ligand binding to the intact LRP (9). This suggests that RAP does not inhibit ligand binding solely in a competitive or sterical manner.…”
mentioning
confidence: 93%
“…Procedures to purify active PAI-1 were essentially as described (25,26). t-PA⅐PAI-1 complexes were prepared as described (9). Human tissue factor pathway inhibitor was a generous gift from Dr. L. Aarden (Central Laboratory of Blood Transfusion, Amsterdam, The Netherlands).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations